U-shaped association between ultra-processed food intake and overactive bladder in US adults: a national cross-sectional study - Zhang, Zufa; Chen, Li; Lv, Long; Li, Wenkai; Hou, Bin; Guan, Sheng; Chen, Zuyi; He, Danni; Song, Hongxuan; Sun, Weibing; Tian, Feng; Jiang, Fengze; et al. (Frontiers in Nutrition, 2025)
BackgroundThe association between ultra-processed food (UPF) intake and overactive bladder (OAB) remains unclear. This study aimed to investigate the relationship between UPF consumption and the risk of OAB in U.S. adults.MethodsWe conducted a cross-sectional analysis using data from 23,482 participants in the National Health and Nutrition Examination Survey (NHANES). UPF intake was assessed in g/day and kcal/day. Perform a natural logarithmic conversion of the UPF with e as the base. Weighted multivariable logistic regression was used to evaluate the association between UPF intake and OAB. Subgroup and interaction analyses were performed to assess effect modification. Restricted cubic spline (RCS) models were applied to explore potential non-linear relationships. Threshold effect analyses were conducted to identify inflection points.ResultsUPF intake was positively associated with the risk of OAB in both continuous and categorical analyses. A U-shaped non-linear relationship between UPF intake and OAB risk was identified, with inflection points at 6.33 (g/day) and 5.73 (kcal/day). Subgroup analyses revealed stronger associations among women, smokers, and overweight or obese individuals. Interaction tests indicated significant modification effects by sex and smoking status.ConclusionThis study suggests a U-shaped association between specific levels of UPF intake and OAB risk among U.S. adults. Further prospective studies are needed to validate these findings and explore the underlying biological mechanisms.